Development and validation of an assay for measurement of leptin in pig saliva. Issue 1 (December 2016) - Schmidt, Elizabeth; Escribano, Damián; Martinez-Subiela, Silvia; Martinez-Miró, Silvia; Hernández, Fuensanta; Tvarijonaviciute, Asta; Cerón, José; Tecles, Fernando
Abstract Background Leptin has been measured in human in saliva samples. However, the low leptin concentration found in this biological fluid makes necessary the use of high sensitive methods. To the authors' knowledge, leptin has not been measured in porcine saliva. This study aimed to develop and validate a time-resolved immunofluorometric assay (TR-IFMA) for salivary leptin measurements in pigs, using a species-specific antibody, and to evaluate how salivary leptin changes with body weight, food ingestion, and in experimental models of stress and inflammation. Polyclonal antibodies were produced in rabbits immunized with recombinant porcine leptin and used to develop a sandwich TR-IFMA. Results The method had intra-assay and inter-assay coefficients of variation lower than 10 and 16 %, respectively. The assay was accurate and the low limit of detection allowed detection of leptin in all analyzed samples. Salivary leptin concentration was positively correlated to body weight (r  = 0.58, P  = 0.01) and increased after food ingestion (P  < 0.001) and after 24 h of applying a model of experimental inflammation by turpentine injection (P  < 0.05). However, it did not significantly change after a model of acute stress consisting of a nose snare restraining. Conclusion These results indicate that the developed assay can measure leptin in porcine saliva in a reliable way and that leptin in saliva is influenced by body weight, food ingestion and inflammation.